2018
DOI: 10.1038/s41438-018-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

A NAC transcription factor, NOR-like1, is a new positive regulator of tomato fruit ripening

Abstract: Ripening of the model fruit tomato (Solanum lycopersicum) is controlled by a transcription factor network including NAC (NAM, ATAF1/2, and CUC2) domain proteins such as No-ripening (NOR), SlNAC1, and SlNAC4, but very little is known about the NAC targets or how they regulate ripening. Here, we conducted a systematic search of fruit-expressed NAC genes and showed that silencing NOR-like1 (Solyc07g063420) using virus-induced gene silencing (VIGS) inhibited specific aspects of ripening. Ripening initiation was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
175
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 77 publications
8
175
0
Order By: Relevance
“…Evidence from other recent work (Gao et al , ) has confirmed that other TFs, including NACs, also modulate expression of genes involved in cell wall metabolism. There is some evidence that RIN interacts with a NAC protein, NAC4 (Zhu et al , ), and may also form heterodimers with other MADS TFs, such as TAGL1, AGL11 and FUL1/2 (reviewed in Li et al , ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Evidence from other recent work (Gao et al , ) has confirmed that other TFs, including NACs, also modulate expression of genes involved in cell wall metabolism. There is some evidence that RIN interacts with a NAC protein, NAC4 (Zhu et al , ), and may also form heterodimers with other MADS TFs, such as TAGL1, AGL11 and FUL1/2 (reviewed in Li et al , ).…”
Section: Discussionmentioning
confidence: 71%
“…RIN expression is enhanced by ethylene (Giovannoni et al , ; Li et al , ; Lü et al , ). Other factors such as NOR, NOR‐like1, ERFs, ARFs and TAGL1, not mentioned in this model, also are involved in the ripening genetic programme (Li et al , ; Gao et al , ). (b) A model of the role of RIN and ET in regulating tomato fruit cell wall changes and softening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these studies, we speculate that the 485 action of the NAC18.1 transgenes was likely attenuated by the dominant-negative activity of the 486 spontaneous nor allele used in our work. Further heterologous characterization of NAC18.1 487 would likely benefit from the use of null nor mutants, or double mutants of nor and nor-like 1 488 (Gao et al, 2018). This may allow for more precise quantitative comparisons between alleles in 489 order to resolve whether differences in the coding sequence of NAC18.1 confer different degrees 490 of ripening.…”
Section: Apple 442mentioning
confidence: 99%
“…With respect to the NAC TF family, functional characterization studies revealed that the NAC members participate in monitoring a wide spectrum of biological processes. Specifically, they have been shown to regulate embryo development [20,21], root development [22,23], shoot development [24], secondary cell wall formation [25,26], reproductive organ development [27,28], fiber development (e.g., in cotton) [29], trichome development [30,31], ripening [32] and senescence [33]. Their regulatory mechanisms have also been demonstrated to be coordinated by various hormone signaling pathways, including abscisic acid (ABA)- [34], jasmonic acid- [35,36], auxin- [37,38], ethylene- [39,40] and gibberellic acid-dependent [41] signaling pathways.…”
Section: Introductionmentioning
confidence: 99%